Prevention and control of cardiovascular disease in “real-world” settings: sustainable implementation of effective policies - Mendis, Shanthi; Graham, Ian (Frontiers in Cardiovascular Medicine, 2024)
Global progress in addressing cardiovascular diseases (CVD) has been insufficient to attain the nine WHO non-communicable disease (NCD) targets and the Sustainable Development Goal (SDG) target of reducing premature NCD mortality by one-third by 2030. Progress has been slowest in low- and middle-income countries (LMIC) where addressing the CVD burden is a foremost development imperative. This review examines the reasons for this situation to propose a way forward. First, we review policy instruments to address behavioral and metabolic risk factors of CVD and health system interventions to improve cardiovascular outcomes. Second, we illustrate the financial, health workforce, health system challenges, and weak national capacity that impede the implementation of these policy instruments. Third, we discuss how LMIC might move forward despite these challenges by (a) giving due consideration to contextual and other factors that determine the success of policy implementation (b) including affordable, high-impact interventions as the core of the universal health coverage health benefit package with primary health care as the foundation and (c) by taking note of the WHO guidance provided in the 2023–2030 implementation roadmap for the Global Action Plan for prevention and control of NCD.